Perancangan Website Portofolio Untuk El Computer Center Dengan Metodologi Waterfall Sebagai Media Pengenalan Dan Promosi Layanan - Fiqhi Nur Hidayatullah, Moh; Mahardika, Ryan; Alfira Lia, Erika; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
El Computer Center faces challenges in expanding its service reach and attracting new customers due to the lack of effective digital promotional media. Reliance on conventional methods, such as pamphlest and word-of-mount, is considered less relevant in today’s digital era. Therefore, this study aims to design and develop a portofolio website as a solution to introduce and promote El Computer Center’s servies more broadly and professionally. The Waterfall software development methodology is used in this study because of its structured approach, string from requirements analysis to maintenance stage. The results of the development show that this website not only increases El Computer Center’s visibility in the digital world but also facilitastes customer access to information technology services. This website server as a strategic solution to support promotional activities and  build better relationships with users.